2017 GPR Observations of the Whillans and Mercer Ice Streams and Modeling Results - Kaluzienski, Lynn (IEDA: US Antarctic Program Data Center, 2020)
Abstract: The dataset includes GPS coordinates for crevasse/fracture locations picked from 350MHz and 400Mhz frequency GPR dataset in the Whillans/Mercer Shear Margin along the SALSA traverse route with associated kinematic outputs for each feature (shear strain rate, vorticity, dilatation). GPS coordinates are in the Antarctic Polar Stereographic projection (EPSG:3031). The dataset also includes initialization and output files of a numerical ice flow simulation of the region . The Ice Sheet System Model (ISSM) model was used to solve a 100 year transient stress balance solution of the region with ~10 kPA/yr friction increase downstream of the shear margin between the Whillans and Mercer ice streams.